ANALISIS RELASI SOSIAL ASOSIATIF ANTAR PEDAGANG PEREMPUAN DI PASAR LINTANG DESA MANDOR KABUPATEN LANDAK - Pani Pani; Yohanes Bahari; Fatmawati Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe title of this research is “analysis of associative social relations between female traders in the Lintang Market Mandor Village Mandor Subdistrict Landak Regency”. The problem in this research is to determine the form of cooperative associative social relations and accommodation embodied in mutual help, mutual cooperation, and mutual agreement between women traders at Lintang Market, Mandor Village, Mandor Subdistrict, Landak Regency. This research includes in qualitative descriptive research. Data collection done by observation, interview and documentation techniques. Sources of data that used are primary data sources and secondary data sources where the main data in qualitative research are words and the rest of the actions are additional data such as documentation and others. Processing techniques and data analysis through three stages, namely (1) data reduction, (2) data presentation and (3) conclusion. The result of this study is the social relationship that exists between female traders in the Lintang Market, Mandor Village, are included in social relations associative due to cooperation and accommodation, the cooperation can evidenced by mutual assistance and mutual cooperation.keywords: social relations, relationship form, female traders